Pemberdayaan Bina Potensi Organisasi Masyarakat Kesenian Sanggar Seni Panglipur Galih Dalam Moderasi Beragama Di Rt 04 Kelurahan Sukamulya - Dwiputri, Aurra Amalia; Aziz, Rohmanur; Geryana Suantara, I Putu Ryan; Pratiwi, Ayu; Nurliza, Tiara; Panida, I Kadek Dwi Jendra (TAFANI: Jurnal Pengabdian Masyarakat, 2025)
Tridharma of higher education, namely community service carried out by RT 04 RW 02, group 05 of the Nusantara Real Work Lecture (KKN) Religious Moderation UIN Sunan Gunung Djati located in Sukamulya Village. Arts and culture are fundamental aspects of community life. In this context, art studios play an important role as centers of activities that not only maintain and develop art, but also as a forum for community empowerment. The researchers found various problems, one of which is related to the arts and artists, especially the Panglipur Galih Art Studio in Sukamulya Village, which always has a variety of arts that attract attention and need support from various parties. The purpose of this service is to be able to explore the potential of art in Sukamulya Village and assist in efforts to increase the potential for community empowerment so that the community will feel a positive impact from the development of the art studio. The expected impact of this empowerment is not only economically but also socially and culturally. This service method certainly leads to steps that have been adjusted by LP2M from cycle I to cycle IV and the empowerment strategy used includes three things. The first is planning, the second is social action and the third is community development of art practitioners. The empowerment results show that the process of community empowerment activity stages initiated by Mr. Caca as the leader of the empowerment from the local community through the procurement of Sanggar Seni Panglipur Galih was carried out through four stages as stated by Wilson, 1996, namely, 1. Awakening (awareness), 2. Understanding (understanding), 3. Harnessing (utilizing), 4. Using (using).